Sistem Monitoring Parameter Fisik Air Kolam Ikan menggunakan Jaringan Sensor Nirkabel berbasis Protokol LoRa - Delarta Tok Adin; Adhitya Bhawiyuga; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Wireless Sensor Network (WSN) is a wireless network composed of individual devices distributed throughout the monitored area. Water monitoring system has been done using ZigBee protocol monitored temperature, dissolved oxygen, and acidity. ZigBee has disadvantages in range aspect so it's not suitable for monitoring in wide area. One of the many protocol that has wide network range is LoRa. LoRa is Low Power Wide Area Wireless Network (LPWAN) for IoT applications. This Research focused on the mechanism of data flow from sensor node to data visualization component. Architecture in this research consist of sensor node, gateway, cloud server and data visualization component. Sensor used are temperature sensor, acidity sensor, turbidity sensor and dissolved oxygen sensor. Data that has been acquired from sensor node then converted into struct. Struct data then sent to gateway using LoRa. Gateway then do the conversion from struct to JSON. Data that has been converted to JSON then will be sent to cloud server to be stored in the database using HTTP protocol. Functionality testing is applied to ensure the system work as it should be. Performance testing is done with successful rate parameter with range and time interval as the variables. Based on that testing this research can be solution to the water monitoring problem especially at the long range monitoring area.